Comparison of Visual Robotic Programming Tools Used in Education - Мордвинов, Дмитрий Александрович; Литвинов, Юрий Викторович (Computer Tools in Education, 2017)
This article provides a detailed survey on educational visual robotic programming tools. Work introduces a set of numeric criteria used for the comparison of widely-used educational robotic programming tools. Also a novel robotic programming environment called TRIK Studio developed by authors is introduced.